â€œUSE OF BIOMASS RESOURCES FROM FOREST AND INDUSTRIAL RELATED ACTIVITIES FOR GENERATION OF ENERGY IN THE ALUMINE AREA, PROVINCE OF NEUQUENâ€ - Gallino, Alejandro; Jatib, MarÃa InÃ©s; Repetto, Horacio; Bentivegna, Marina; Assusa, MarÃa Sol (European Scientific Journal, ESJ, 2015)
The global context shows a significant increase in terms of energy consumption and dependence on fossil fuels, leading to high costs for the population, and its natural and social environment as well. This situation should be tackled in the very short term. Currently, the environmental impact registered has further led to the generation of new alternatives aimed at reducing this impact and maximizing sustainability. Focus has been placed on the development of renewable energy from biomass sources. In Argentina, one feasible proposed alternative consists in using forest waste for the development of bio-energy. The available inventories carried out in the Aluminé area, province of Neuquén, reveal a wide availability of suitable land for forest crops, building the necessary conditions for the forestry sector to become one of the productive activities with greater development possibilities in the Neuquén area. It is thus necessary, to introduce a paradigm shift in the energy matrix, through the use of these biomass resources derived from the forest industry activity. This change will replace, in the mid and long term and to a certain level, fossil fuels which the region currently depends on, and will make possible to achieve, in the near future, the necessary self-sufficiency and sustainability for energy development. This is initially intended for the region, and potentially nationwide.